1986
DOI: 10.2307/2000161
|View full text |Cite
|
Sign up to set email alerts
|

Splitting Strongly Almost Disjoint Families

Abstract: ABSTRACT. We say that a family A C [A]K is strongly almost disjoint if something more than just \A n B\ < n, e.g. that \A f! B\ < a < k, is assumed for A, B G A. We formulate conditions under which every such strongly a.d. family is "essentially disjoint", i.e. for each A E A there is F(A) G [A] Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Magidor [1] showed that the same conclusion follows from Martin's Maximum. Finally, Cummings, Foreman, and Magidor [5] proved that a model of Shelah [9] in which the approachability property AP ℵω fails also satisfies that there is no good scale.…”
Section: No Good Scalesmentioning
confidence: 98%
“…Magidor [1] showed that the same conclusion follows from Martin's Maximum. Finally, Cummings, Foreman, and Magidor [5] proved that a model of Shelah [9] in which the approachability property AP ℵω fails also satisfies that there is no good scale.…”
Section: No Good Scalesmentioning
confidence: 98%
“…The paper [3] is a natural sequel to the paper of Erdös and Hajnal. It answers a number of questions from [2] and considers conditions when almost disjoint families A ⊆ [λ] κ are essentially disjoint: removing a set of size κ from each member produces a disjoint family.…”
Section: Theorem 2 For Each R < ω and Each R-almost Disjoint Familymentioning
confidence: 99%
“…We distinguish two cases. 3 Note that in this argument, as well as in the proof of the next lemma, only the following consequence of weak closedness is used:…”
Section: Proof Assume Towards a Contradiction Thatmentioning
confidence: 99%
“…It turns out that CECA is equivalent to GCH + some previously known weakenings of 2 λ , but CECA has a different flavor than 2 λ -principles and may be easier to work with. The equivalence will be shown in Section 1.In [3] it is shown that under certain conditions almost disjoint families {A α : α < κ} can be refined to disjoint families by removing small sets A α from each A α . Let us say that a family {A α : α < κ} is point-< τ if for every I ∈ [κ] τ the intersection α∈I A α is empty.…”
mentioning
confidence: 99%
See 1 more Smart Citation